2010
DOI: 10.1080/01635580903305276
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Information Needs of Medical Oncology Patients Receiving Treatment at an Australian Public Hospital

Abstract: This study aimed to identify 1) the prevalence of malnutrition according to the scored Patient Generated-Subjective Global Assessment (PG-SGA), 2) utilization of available nutrition resources, 3) patient nutrition information needs, and 4) external sources of nutrition information. An observational, cross-sectional study was undertaken at an Australian public hospital on 191 patients receiving oncology services. According to PG-SGA, 49% of patients were malnourished, and 46% required improved symptom managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 30 publications
2
34
1
Order By: Relevance
“…Nutrition impact symptoms (Table 2) were common, with 59 % of patients experiencing at least one of these symptoms in the 2 weeks preceding nutritional assessment. This is comparable with previous studies by Isenring et al [3], which found that 48 % of participants (N = 191) had at least one nutrition impact symptom, and Khalid et al [21], who reported that 62 % (N = 161) of patients had at least one nutrition impact symptom. There were a number of components (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nutrition impact symptoms (Table 2) were common, with 59 % of patients experiencing at least one of these symptoms in the 2 weeks preceding nutritional assessment. This is comparable with previous studies by Isenring et al [3], which found that 48 % of participants (N = 191) had at least one nutrition impact symptom, and Khalid et al [21], who reported that 62 % (N = 161) of patients had at least one nutrition impact symptom. There were a number of components (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence-based practice guidelines recommend the use of the Scored PatientGenerated Subjective Global Assessment (PG-SGA) for nutrition assessment within the oncology patient population [1]. However, comprehensive nutrition assessment is not practical for routine use for all oncology patients in large tertiary hospitals due to time and human resource limitations [3]. It is therefore appropriate to consider a more simplified yet accurate screening process to identify patients at nutritional risk.…”
Section: Introductionmentioning
confidence: 98%
“…A recent observational study in 191 oncology patients receiving cancer services at a public Australian hospital found that almost one half of patients were malnourished, and common symptoms impacting on dietary intake included taste changes, poor appetite and nausea (Isenring et al 2010). Consequences of malnutrition include increased risk of infections, poor wound healing, decreased quality of life and transfer to higher level care (Watterson et al 2009).…”
Section: Malnutrition Is Common In Patients With Cancermentioning
confidence: 99%
“…Many patients are interested in nutrition and seek nutritional advice external to the cancer centre. It has been reported that 40% of cancer patients are seeking extra nutrition resources and would like further information regarding dietary tips for managing side effects and supplements (Isenring et al 2010). Therefore it is important that health professionals feel comfortable answering common nutritional queries using an evidence-based approach, have access to appropriate resources e.g.…”
Section: Nutrition and Physical Activity Recommendations For Cancer Smentioning
confidence: 99%
“…The incidence of malnutrition among patients with cancer has been estimated at between 40 and 80% [5,6,7,8]. Nearly 20% of cancer patients are reported to die of malnutrition or its associated complications rather than the malignant disease itself [9].…”
Section: Introductionmentioning
confidence: 99%